Novel SCA19/22‐associated KCND3 mutations disrupt human KV4.3 protein biosynthesis and channel gating. Issue 11 (17th August 2019) - Hsiao, Cheng‐Tsung; Fu, Ssu‐Ju; Liu, Yo‐Tsen; Lu, Yi‐Hsiang; Zhong, Ciao‐Yu; Tang, Chih‐Yung; Soong, Bing‐Wen; Jeng, Chung‐Jiuan
Abstract: Mutations in the human voltage‐gated K + channel subunit KV 4.3‐encoding KCND3 gene have been associated with the autosomal dominant neurodegenerative disorder spinocerebellar ataxia types 19 and 22 (SCA19/22). The precise pathophysiology underlying the dominant inheritance pattern of SCA19/22 remains elusive. Using cerebellar ataxia‐specific targeted next‐generation sequencing technology, we identified two novel KCND3 mutations, c.950 G>A (p.C317Y) and c.1123 C>T (p.P375S) from a cohort with inherited cerebellar ataxias in Taiwan. The patients manifested notable phenotypic heterogeneity that includes cognitive impairment. We employed in vitro heterologous expression systems to inspect the biophysical and biochemical properties of human KV 4.3 harboring the two novel mutations, as well as two previously reported but uncharacterized disease‐related mutations, c.1013 T>A (p.V338E) and c.1130 C>T (p.T377M). Electrophysiological analyses revealed that all of these SCA19/22‐associated KV 4.3 mutant channels manifested loss‐of‐function phenotypes. Protein chemistry and immunofluorescence analyses further demonstrated that these mutants displayed enhanced protein degradation and defective membrane trafficking. By coexpressing KV 4.3 wild‐type with the disease‐related mutants, we provided direct evidence showing that the mutants instigated anomalous protein biosynthesis and channel gating of KV 4.3. We propose that the dominant inheritance pattern of SCA19/22 may be explained by the dominant‐negative effects of the mutants on protein biosynthesis and voltage‐dependent gating of KV 4.3 wild‐type channel. Abstract : Schematic model of the dominant‐negative mechanisms of SCA19/22.